Lead Induced Hepato-renal Damage in Male Albino Rats and Effects of Activated Charcoal - Offor, Samuel J.; Mbagwu, Herbert O. C.; Orisakwe, Orish E. (Frontiers in Pharmacology, 2017)
Lead is a multi-organ toxicant implicated in various cancers, diseases of the hepatic, renal and reproductive systems etc. In search of cheap and readily available antidote this study has investigated the role of activated charcoal in chronic lead exposure in albino rats. Eighteen mature male albino rats were used, divided into three groups of six rats per group. Group 1 (control rats) received deionised water (10ml/kg), group 2 was given lead acetate solution 60mg/kg and group 3 rats were given lead acetate (60mg/kg) followed by Activated charcoal, AC (1000mg/kg) by oral gavage daily for 28 days. Rats in group 2 showed significant increases in serum AST, ALP, ALT, urea, bilirubin, total cholesterol, triglycerides, LDL, VLDL, total WBC, MDA, IL-6 and decreases in PCV, haemoglobin concentration, RBC count, total proteins, albumins, SOD, glutathione peroxidase and total glutathione. Co-administration of AC significantly decreased these biomarkers with the exception of the sperm parameters. Histopathology of liver and kidney also confirmed the protective effective of AC against lead induced hepato-renal damage. AC may be beneficial in chronic lead induced liver and kidney damage.